Dynamics of Blended Learning in the Covid-19 Pandemic in Integrated Islamic Education Institutions - Supardi Supardi (UIN Sunan Gunung Djati Bandung, 2022)
Blended learning is an approach that integrates e-learning methods with traditional methods (face-to-face interactions) simultaneously at certain periods. This study elaborates on the dynamics of blended learning implementation during the Covid-19 pandemic at SD IT Fauziah Yarsi Mataram, an integrated Islamic education institution in West Nusa Tenggara, Indonesia. The research method used is a qualitative research method in which the researcher was a key instrument in conducting interviews, field observations and reviewing documentation related to implementing blended learning in schools. The results of this study show that during the Covid-19 pandemic, SD IT Fauziah Yarsi Mataram implemented blended learning limited to the subjects of Qur'an, Hadith, and Fiqh. At the same time, the instruction of general material subjects such as mathematics, languages, and social studies was carried out using e-learning methods. The applied blended learning involved the components of collaboration, online content, and assessment intended to increase students' motivation and learning outcomes and overcome the psychological problems faced by the students during the pandemic. The application of blended learning in Qur'an, Hadith, and Fiqh manifested the school's vision and mission and considering that these subjects are part of the school's prime programs.